Inferring causation from time series in Earth system sciences - Jakob Runge (Nature Portfolio, 2019)
Questions of causality are ubiquitous in Earth system sciences and beyond, yet correlation techniques still prevail. This Perspective provides an overview of causal inference methods, identifies promising applications and methodological challenges, and initiates a causality benchmark platform.